Technology and tuberculosis control: the OUT-TB Web experience. (2nd September 2016) - Guthrie, Jennifer L; Alexander, David C; Marchand-Austin, Alex; Lam, Karen; Whelan, Michael; Lee, Brenda; Furness, Colin; Rea, Elizabeth; Stuart, Rebecca; Lechner, Julia; Varia, Monali; McLean, Jennifer; et al.
Abstract : Objective: Develop a tool to disseminate integrated laboratory, clinical, and demographic case data necessary for improved contact tracing and outbreak detection of tuberculosis (TB). Methods: In 2007, the Public Health Ontario Laboratories implemented a universal genotyping program to monitor the spread of TB strains within Ontario. Ontario Universal Typing of TB (OUT-TB) Web utilizes geographic information system (GIS) technology with a relational database platform, allowing TB control staff to visualize genotyping matches and microbiological data within the context of relevant epidemiological and demographic data. Results: OUT-TB Web is currently available to the 8 health units responsible for >85% of Ontario's TB cases and is a valuable tool for TB case investigation. Users identified key features to implement for application enhancements, including an e-mail alert function, customizable heat maps for visualizing TB and drug-resistant cases, socioeconomic map layers, a dashboard providing TB surveillance metrics, and a feature for animating the geographic spread of strains over time. Conclusion: OUT-TB Web has proven to be an award-winning application and a useful tool. Developed and enhanced using regular user feedback, future versions will include additional data sources, enhanced map and line-list filter capabilities, and development of a mobile app.